A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages for the first time will normally be required to serve for a period as assistants to more experienced practitioners, and the Board will be able to require them to give full time to the service if necessary. (j) Compensation will be paid to any doctor who loses the value of his practice — e.g. by entering a Health Centre or because he is prohibited from transferring the practice to another doctor on the ground that there are too many doctors in the area. Superannuation schemes will be provided for doctors in Health Centres and the possibility of providing them in other forms of practice will be discussed with the profession, and the practicability of abolishing the sale and purchase of public practices will be similarly discussed. (k) Arrangements for the supply of drugs and medical appliances will be considered and discussed with the appropriate bodies. 5. Clinics and other services. (a) It will be the duty of the joint authority to include in its area plan provision for all necessary clinics and other local services (e.g., child welfare, home nursing, health visiting, midwifery and others), and to provide for the co-ordination of these services with the other services in the plan. (b) County and county borough councils will normally provide most of these local services. The exact allocation of responsibility between the joint authority and the individual county and county borough councils will be finally settled in each case in the approved area plan; but the principle will be that services belonging to the hospital and consultant sphere will fall to the joint authority while other local and clinic services will fall to the individual councils. (c) Child welfare duties will always fail to the authority responsible for child education under the new Education Bill. (d) New forms of service, e.g., for general dentistry and care of the eyes, will be considered with the professional and other interests concerned. In the case of dentistry the report of the Teviot Committee is awaited. 6. Organisation in Scotland. (a) The scope and objects of the service will be the same in Scotland as in England and Wales, but subject to certain differences due to special circumstances and the geography and existing local government structure in Scotland. (b) The local organisation in Scotland will differ from that in England and Wales and will be on the following lines :— (i) Regional Hospitals Advisory Councils will be set up for each of five big regions. The Councils will be advisory to the 31 36/H24/41